2010
DOI: 10.1038/ja.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the biosynthetic gene cluster for naphthoxanthene antibiotic FD-594 from Streptomyces sp. TA-0256

Abstract: FD-594 is an unique pyrano [4¢,3¢:6,7]naphtho [1,2-b]xanthene polyketide with a trisaccharide of 2,6-dideoxysugars. In this study, we cloned the FD-594 biosynthetic gene cluster from the producer strain Streptomyces sp. TA-0256 to investigate its biosynthesis. The identified pnx gene cluster was 38 143 bp, consisting of 40 open reading frames, including a minimal PKS gene, TDP-olivose biosynthetic genes, two glycosyltransferase genes, two methyltransferase genes and many oxygenase/reductase genes. Most of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Biosynthesis of the polyketide core structures of seven of the sixteen pentangular, tetracenomycin, or related unique training set compounds are known or predicted to be initiated by incorporation of a non-acetate starter unit [ 38 , 39 42 ]. In each case, a type III ketosynthase or stand-alone adenylation domain is present in the gene cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biosynthesis of the polyketide core structures of seven of the sixteen pentangular, tetracenomycin, or related unique training set compounds are known or predicted to be initiated by incorporation of a non-acetate starter unit [ 38 , 39 42 ]. In each case, a type III ketosynthase or stand-alone adenylation domain is present in the gene cluster.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore possible that ABM superfamily members FkmO1 and FkmO2 and their homologues may be involved in pentangular polyketide cyclization. In light of the conservation of homologues of both proteins in the eleven pentangular clusters sequenced thus far [ 5 , 6 , 39 42 , 55 60 ] but not in tetracenomycin class clusters; and the conserved adjacent co-directional arrangement of their encoding genes, we hypothesize that both FkmO1 and FkmO2 and their homologues are immediate tailoring enzymes that may be involved in B ring oxygenation and/or E ring cyclization and aromatization ( Fig. 8 , Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study on FD-594 ( 5 ) suggested rather an epoxidation followed by a Baeyer-Villiger oxidation was involved in the formation of the xanthone ring. 16 …”
Section: Structurementioning
confidence: 99%
“…Many type I PKS gene clusters and non-ribosomal peptide gene clusters are very large, for example, the biosynthetic gene cluster of type I polyketides for biosynthesis of a 51-membered macrolide complex in Streptomyces ambofaciens can be as large as 150 kb (Laureti et al, 2011b), which makes it difficult to accommodate the gene clusters in one single cosmid due to size limitation (Hu et al, 2005;Kudo et al, 2011;Lohman et al, 2013). Although bacterial artificial chromosome (BAC) vectors are widely used to carry large gene clusters such as type I polyketide gene clusters and non-ribosomal peptide gene clusters (Miao et al, 2005;Perlova et al, 2006a;Molnar et al, 2000), manipulation of very large fragments on single vector remains challenging, and the production titer may be limited by the low copy number of the BAC vector.…”
Section: Introductionmentioning
confidence: 99%